Android-based smart energy monitoring system - Goh, You Sheng (2023)
With the increasing awareness of the need to protect the environment, promoting energy saving has become an urgent concern for individuals and businesses. As a household electricity user, it can be challenging to avoid energy waste at all times. This can lead to excessive energy consumption and harmful carbon emissions. Therefore, this project aims to increase energy efficiency by managing smart wall outlets via a mobile application. The project focuses on the iterative development of a mobile application using the React Native and NodeJS frameworks. This application allows users to remotely control the status of the wall outlet and receive notifications regarding the status of the wall outlet, resulting in improved energy management and conservation. The usability of the mobile application has been a vital aspect of the project, and the app features voice recognition to facilitate its use in different scenarios by different users. This project has far-reaching implications for energy management and the environment, as users no longer need to keep track of the status of dozens or even hundreds of sockets in person, leading to better energy conservation and carbon reduction. Moreover, planning the status of the wall outlets in advance through task scheduling allows for even greater energy efficiency and conservation. Overall, this project represents a step towards better environmental stewardship and responsibility. By developing an app that effectively manages smart wall outlets and reduces unnecessary energy usage, this project contributes to the ongoing efforts to protect the environment and preserve our planet for future generations.